Protective Effect of Temulawak (Curcuma xanthorriza) Rhizome Extract on Monosodium Glutamate-Induced Mice Sperm - Aris Soewondo; Yuyun Indriani Kartiko Santi; Agung Pramana Warih Marhendra; Sri Rahayu (Universitas Brawijaya, 2023)
The current study aimed to analyze the protective effect of the aqueous extract of temulawak (Curcuma xanthorriza) rhizome on the sperm quality of monosodium glutamate (MSG)-induced mice. This study used 30 male mice (aged 2.5-3 months old and weighing 25-30 g), which were then randomly divided into five groups: K- (healthy male mice received only aquadest), K+ (male mice exposed to 4 mg/kg BW MSG), MT1, MT2 and MT3 (MSG-induced male mice orally treated with 0.2, 0.4 and 0.6 mg/g BW temulawak (C. xanthorriza) rhizome extract for 14 days, respectively). At the end of treatment, all mice were sacrificed, and cauda epididymis was isolated. The obtained semen was analyzed for its quality, including motility, viability, concentration and spermatozoa abnormalities. MT2 group exhibited the highest sperm motility of MSG-induced mice (79.16±4.45%). The highest sperm viability was also observed in the MT2 (77.83±2.75%) followed by MT1 and MT3 groups (70.19±5.93 and 72.41±5.53%, respectively). MT2 and MT3 groups could increase (p<0.05) sperm concentration in MSG-induced mice by 14.03x106 and 14.46x106 cells/ml, respectively. While, sperm abnormalities of MSG-induced mice tend to decrease in all groups treatment by 38.10% (MT1), 36.32% (MT2) and 36.04% (MT3). In conclusion, the administration of 0.4 mg/g BW aqueous extract of C. xanthorriza rhizome could improve sperm quality by increasing the motility, viability and concentration of sperm and also altered the sperm abnormality of MSG-induced mice.